Study on drying kinetics of summer onion (Bangladesh Journal of Agricultural Research, 2015)
The present study was concerned with the kinetics of drying of summer onion. Drying was done in a mechanical dryer at constant air flow using blanched and unblanched onion with variable temperature (52, 60 and 680C) and thickness (3, 5 and 7 mm). Drying rate was increased with increase of temperature and decreased with the increase in thickness in blanched and unblanched onion. Blanched onion showed higher drying rate than unblanched onion. Drying rate constant and thickness can be expressed as power low equations. The value of index n were found to be 1.277 and 0.845 for onion indicating that the external resistance to mass transfer was highly significant. The effect of temperature on diffusion co-efficient follows an Arrhenius type relationship. The activation energy (Ea) for diffusion of water was found 5.781 Kcal/g-mole for unblanched and 2.46 Kcal/g-mole for blanched onion when onions were dried in mechanical dryer. DOI: http://dx.doi.org/10.3329/bjar.v39i4.22545 Bangladesh J. Agril. Res. 39(4): 661-673, December 2014